Unprecedented Catalytic Behavior of Uranyl(VI) Compounds in Chemical Reactions. Issue 2 (20th November 2020) - Behera, Nabakrushna; Sethi, Sipun
Abstract : Uranyl catalysis represents a progressively more significant class of current research. The key species responsible for such catalysis is UO2 2+ ion which is a remarkably stable molecular component possessing strongly covalent and chemically robust trans U‐oxo groups. Aside from its fundamental interest, an understanding of the chemistry of such divalent UO2 2+ ion is enviable due to its huge ecological importance. The unprecedented electronic non‐rigidity of uranium center with easy switching among oxidation states and kinetic lability of its coordination states are the key features to bring about a considerable development in its catalytic reactivity profiles. This review explores the topical evolutions of most promising uranyl(VI) catalytic systems appearing in the literature for the last two decades along with reports prior to 2000 incorporated where pertinent. In addition to homometallic uranyl catalysis, a succinct discussion on heterometallic uranyl catalysis is presented. Finally, some relevant comparisons have been made between the uranyl catalysis and transition metal systems. Abstract : Owing to the electronic flexibility, easy switching among oxidation states, and the kinetic lability of coordination states, there is a significant growth in the catalytic reactivity profiles of uranyl based compounds. This review intends to provide both thermal‐ as well as photocatalytic processes of the most promising uranyl(VI) compounds.